EU-Beitritt: Freizügigkeit für Arbeitskräfte aus der Ukraine und Republik Moldau - Matthias Lücke (Wirtschaftsdienst, 2024)
– In the 2004 Eastern enlargement, free movement in the EU for citizens of the new member states applied only from the date of accession - or even later in those 'old' member states that used long transition periods. However, refugees from Ukraine now live and work freely throughout the EU and many Moldovans hold Romanian passports. With free movement, there would be little extra impact on labour markets; people's legal status would be secured (current protection for Ukrainians runs out in 2025); and EU accession would become an even stronger institutional anchor for the ongoing systemic transformation of both countries.
Keywords: F15; F22; 330; Freizügigkeit; EU-Staaten; Moldawien; Ukraine; Freizügigkeit; EU-Staaten; Moldawien; Ukraine